Description of the widely reported terebellid polychaetes Loimia medusa (Savigny) and Amphitrite rubra (Risso). In: Keyser, Dietmar; Whatley, Robin C. (Eds.). Zur Zoogeographie und Systematik insbesondere der Polychaeten und Ostracoden: zu ehren von Dr. habil. Gesa Hartmann-Schröder und Prof. Dr. h. c. Gerhard Hartmann. - Hutchings, Patricia A.; Glasby, Christopher J. (Mitteilungen aus dem Hamburgischen Zoologischen Museum und Institut, 1995)
The identity of the two terebellid polychaetes Loimia medusa (Savigny) and Amphitrite rubra (Risso) has been uncertain, partly due to the brief original descriptions. To rectify this problem both species are redescribed. A neotype is erected for Loimia medusa, based on a specimen from the Red Sea. The paratype of Amphitrite rubra is redescribed as indeterminate and it is suggested that the specimen represents a new genus of Terebellidae.
World Polychaeta Database (WPolyDb)